Advances in Cryptology-CRYPTO ’94: 14th Annual International Cryptology Conference Santa Barbara, California, USA August 21–25, 1994 Proceedings - Desmedt, Yvo G. (Lecture notes in computer science, 1994)
This volume constitutes the proceedings of CRYPTO '94, the 14th International Cryptology Conference, held at Santa Barbara, CA, USA in August 1994 under the sponsorship of the International Association for Cryptologic Research (IACR). The proceedings contains revised versions of the 38 papers selected for presentation at the conference from a total of 114 submissions. All aspects of cryptologic research and advanced applications are addressed; in particular there are sections on block ciphers, signatures, implementation and hardware aspects, authentication and secret sharing, zero-knowledge, combinatorics, number theory, cryptanalysis and protocol failures, and secure computations and protocols
Literaturangaben
Keywords: Konferenzschrift -- 1994 -- Santa Barbara, Calif.; Kryptologie